Secondary batteries and battery packs
Patent Information
- Application Number
- JP2024503496
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-01-09
- Filing Date
- 2023-08-30
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-08-30
Smart Images

Figure 2025505079000012 
Figure 2025505079000013 
Figure 2025505079000014
Abstract
Description
[Technical field]
[0001] This application claims priority to a Chinese patent application, application number 202310030037.8, filed with the China Patent Office on January 9, 2023, for the invention titled "Secondary Battery and Battery Pack," the entire contents of which are incorporated herein by reference.
[0002] The present application relates to the field of battery technology, and more particularly to secondary batteries and battery packs. [Background technology]
[0003] With the rapid development of electric vehicles and digital electronic products, there is a demand for power secondary batteries with higher power density, energy density and suitable for rapid charging and discharging to be applied in the fields of electric vehicles and related electronic products. For secondary batteries such as lithium ion batteries, increasing the energy density of the lithium ion battery is one of the direct and effective ways to improve the driving range of the lithium ion battery.
[0004] A high energy density secondary battery requires higher material packing density and less auxiliary material to provide space for the active material, whereas when designing a secondary battery for high rate discharge, a relatively low material packing density, more conductive material and thicker current collector are required to achieve high rate discharge performance, thereby avoiding deterioration of cycle performance due to overheating and lithium precipitation.
[0005] Therefore, there is a need to provide a secondary battery that has high multiplication performance without affecting the energy density of the secondary battery. Summary of the Invention
[0006] In a first aspect, the present application provides a secondary battery, the secondary battery including a negative electrode sheet, the negative electrode sheet including a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, the negative electrode active material layer including a negative electrode active material, the negative electrode active material including a carbon material, and the crystal grain size of the negative electrode active material is XS nm. The non-Faraday capacity of the negative electrode sheet is Cdl nF, 0.05≦Cdl≦10, where:
number
[0007] In some embodiments, 0.01≦XS≦6.
[0008] In some embodiments, the pore volume of the negative electrode active material is α cm 3 / g, and 0.5≦Cdl+10×α≦8.
[0009] In some embodiments, the pore volume of the negative electrode active material is α cm 3 / g, and 0.001≦α≦0.5.
[0010] In some embodiments, the negative electrode active material has a powder resistivity of R Ω·cm at 20 KN, and 0.01≦10R / Cdl≦5.
[0011] In some embodiments, the negative electrode active material has a powder resistivity R Ω·cm at 20 KN, where 0.002≦R≦2.
[0012] In some embodiments, the secondary battery further includes a positive electrode sheet, the positive electrode sheet including a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, the positive electrode active material layer including a positive electrode active material.
[0013] In some embodiments, the particle size distribution of the negative electrode active material is A, and the particle size distribution of the positive electrode active material is B, and A and B satisfy at least one of the following characteristics: (a) 0.5≦A≦2.5; (b) 1.0≦B≦5.0; (c) 0.5≦B / A≦2.5.
[0014] In some embodiments, the negative electrode active material layer has a thickness of C μm and the positive electrode active material layer has a thickness of D μm, and C and D satisfy at least one of the following characteristics: (i) 99≦C≦160; (ii) 80≦D≦130; (iii) 0.1≦1−(D / C)≦0.5.
[0015] In some embodiments, the surface of the negative electrode active material is coated with a first coating layer, and the first coating layer has a thickness H1 nm, where 5≦H1≦200 and 10≦Cdl×H1≦250.
[0016] In some embodiments, the surface of the positive electrode active material is coated with a second coating layer, and the second coating layer has a thickness H2 nm, where 5≦H2≦60.
[0017] In a second aspect, the present application further provides a battery pack, which includes the above-mentioned secondary battery. [Brief description of the drawings]
[0018] [Figure 1] 1 is a fitting curve of a scanning speed-current scatter diagram of the negative electrode sheet prepared in Example 1 of the present application. [Diagram 2] 1 shows test results for the secondary batteries produced in Examples 1 to 20 of the present application. [Diagram 3] 1 shows test results for the secondary batteries produced in Examples 21 to 30 and Comparative Examples 1 to 4 of the present application. [Figure 4] 1 shows test data results and test results of cycle performance and power supply performance for the secondary batteries produced in Examples 1 to 20 of the present application. [Diagram 5]1 shows test data results and test results of cycle performance and power supply performance for the secondary batteries produced in Examples 21 to 30 and Comparative Examples 1 to 4 of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The present application provides a secondary battery and a battery pack, and in order to more clearly and embody the objectives, technical ideas, and effects of the present application, the present application will be described in more detail below by way of examples with reference to the drawings. It should be understood that the specific examples described in the present specification are merely for the purpose of illustrating the present application, and are not intended to limit the present application.
[0020] The embodiments of the present application provide a secondary battery and a battery pack having the secondary battery, in which the non-Faraday capacity of the negative electrode sheet is controlled within a predetermined range, and at the same time, the grain size of the negative electrode active material and the non-Faraday capacity of the negative electrode sheet are controlled within a predetermined range, thereby increasing the number of electrochemical active points on the surface of the negative electrode sheet in the secondary battery, favoring the contact between the negative electrode active material and the electrolyte, accelerating the conduction speed of ions and electrons, and reducing the charge transport resistance; at the same time, increasing the actual contact area between the negative electrode sheet and the electrolyte, shortening the distance of ion and electron transport, increasing the number of reactive active points on the surface of the negative electrode sheet, improving the non-Faraday reaction strength, and making the secondary battery have a smaller charge transfer resistance, thereby greatly improving the multiplication performance of the secondary battery.
[0021] An embodiment of the present application provides a secondary battery, which includes a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte, and a housing.
[0022] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, the negative electrode active material layer including a negative electrode active material, and the negative electrode active material includes a carbon material.
[0023] The negative electrode sheet is a single-sided sheet or a double-sided sheet, and when the negative electrode sheet is a single-sided sheet, the negative electrode active material layer is disposed on one surface of the negative electrode current collector, and when the negative electrode sheet is a double-sided sheet, the negative electrode active material layer is disposed on both surfaces of the negative electrode current collector. The negative electrode sheet may simultaneously have a single-sided negative electrode sheet region and a double-sided negative electrode sheet region.
[0024] In some embodiments, the negative electrode active material includes graphite. In some embodiments, the relationship between the grain size XS of the negative electrode active material and the non-Faraday capacity Cdl of the negative electrode sheet is
number
number
[0025] In some embodiments, the relationship between XS and Cdl is:
number
[0026] In some embodiments, the relationship between XS and Cdl is:
number
[0027] In some embodiments, the non-faradaic capacity of the negative electrode sheet is Cdl nF, and the numerical range of Cdl is 0.05≦Cdl≦10, and specifically, Cdl may be any of 0.05, 0.1, 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10, or a range consisting of any two numbers therein. The faradaic reaction in a secondary battery is a process in which the oxidation state of an active material changes and charge is transferred through a double charge layer through the electrode interface into the active material. Non-Faraday reactions are reactions in which charges are stored and released by ions being physically adsorbed and released on the electrode surface without causing charge transfer through the electrode interface. The non-Faraday capacitance value Cdl indicates the number of electrochemically active sites on the negative electrode sheet. Within a certain range, increasing Cdl increases the number of electrochemically active sites, which is favorable for the contact between the negative electrode active material and the electrolyte, accelerating the rate of ion-electron conduction, reducing the resistance of charge transport, and effectively improving the charging rate performance of the secondary battery.
[0028] In some embodiments, 0.1≦Cdl≦10, and when the non-Faraday capacity value of the negative electrode sheet satisfies the above range, the overall performance of the secondary battery is further improved.
[0029] In some embodiments, 0.5≦Cdl≦9. When the non-Faraday capacity value of the negative electrode sheet satisfies the above range, the internal structure of the negative electrode sheet can be further optimized, and the number of electrochemically active sites on the surface of the negative electrode sheet can be in a more suitable range, so that the overall performance of the secondary battery can be further improved.
[0030] In some embodiments, when the non-Faraday capacity value of the negative electrode sheet satisfies the above range, the overall performance of the secondary battery is well-balanced, and the overall performance of the secondary battery can be improved.
[0031] In some embodiments, the grain size of the negative electrode active material is XS nm, and the numerical range of XS is 0.01≦XS≦6, specifically, XS may be any of 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, or a range consisting of any two numbers therein. The grain size XS is obtained by performing a refinement process on the XRD pattern of the negative electrode active material, and the measurement conditions of the XRD are to adopt a stepwise scan, set the step size≦0.02°, set the dwell time ≧2s, and set the scan range to 10° to 90°.
[0032] The electron conduction characteristics affect the multiplication performance of the secondary battery, and the crystal grain size XS may affect the high voltage, high temperature cycle, and high current capacity of the secondary battery. Research has shown that an increase in the charge transfer activation energy and ion diffusion activation energy of the negative electrode active material will inhibit the reaction between the negative electrode sheet and the electrolyte interface to a certain extent, thus affecting the properties of the negative electrode active material. Controlling the crystal grain size XS of the negative electrode active material can affect the actual contact area between the negative electrode sheet and the electrolyte, shorten the distance of ion-electron transport, increase the number of reactive active points on the surface of the negative electrode sheet, improve the non-Faraday reaction strength, and have a smaller charge transfer resistance, thereby greatly improving the multiplication performance of the secondary battery. The crystal grain size can be controlled by the particle size of the negative electrode active material, the graphitization temperature, the graphitization time, doping modification and other means. Therefore, the relationship between the crystal grain size value XS of the non-negative electrode active material of the negative electrode sheet and the non-Faraday capacity value Cdl of the negative electrode sheet can be calculated as follows:
number
[0033] In some embodiments, the grain size of the negative electrode active material is XS nm, and the numerical range of XS is 0.1≦XS≦5.5. When the grain size of the negative electrode active material satisfies the above range, the negative electrode active material exhibits excellent high voltage and high temperature cycle and high current capacity, and the actual contact area between the electrolyte and the negative electrode active material granules is in a more suitable range, so that the overall performance of the secondary battery is further improved.
[0034] In some embodiments, the negative electrode active material has a grain size of XS nm, and the numerical range of XS is 0.2≦XS≦5. When the grain size of the negative electrode active material satisfies the above range, the overall performance of the secondary battery can be further improved.
[0035] In some embodiments, the negative electrode active material has a grain size of XS nm, where XS is in the numerical range of 0.4≦XS≦4.5.
[0036] In some embodiments, the negative electrode active material has a grain size of XS nm, where XS is in the numerical range of 0.4≦XS≦4.2.
[0037] In some embodiments, the negative electrode active material has a grain size of XS nm, where XS is in the numerical range of 0.52≦XS≦3.9.
[0038] In some embodiments, the pore volume of the negative electrode active material is 3The relationship between the pore volume α cm3 / g and the non-Faraday capacity Cdl nF of the negative electrode sheet is 0.5≦Cdl+10×α≦8, and specifically, the numerical range of Cdl+10×α may be any one of 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, and 8.0, or a range consisting of any two of these numbers. 3 / g refers to the total pore volume per unit mass of the porous solid. When Cdl+10×α is within the above range, the negative active material has many pore structures, which improves the contact area between the negative electrode sheet and the electrolyte, further shortens the lithium ion transport path, realizes rapid impregnation of the electrolyte, allows the lithium ions to be rapidly absorbed and released on the surface of the negative electrode material, accelerates the reaction kinetics, reduces the polarization on the negative electrode surface, makes the current distribution more uniform, and when charging at a high rate, more negative active materials can simultaneously absorb Li. + This effectively avoids lithium deposition on the negative electrode surface.
[0039] In some embodiments, the pore volume of the negative electrode active material is 3 The relationship between / g and the non-Faraday capacity Cdl nF of the negative electrode sheet is 0.8≦Cdl+10×α≦6.8. When Cdl+10×α satisfies the above range, the negative electrode sheet can provide sufficient electrochemical reaction active sites in the electrochemical process, accelerate the non-Faraday reaction process of the negative electrode, favor the transfer of electrons and ions between the solid phase and the liquid phase, improve the electrochemical reaction kinetics, and further improve the multiplication performance of the material.
[0040] In some embodiments, the pore volume of the negative electrode active material is 3 The relationship between the amount of α / g and the non-Faraday capacity Cdl nF of the negative electrode sheet is 1.1≦Cdl+10×α≦6.2.
[0041] In some embodiments, the pore volume of the negative electrode active material is 3The relationship between / g and the non-Faraday capacity Cdl nF of the negative electrode sheet is 1.3≦Cdl+10×α≦5.9. When Cdl+10×α satisfies the above range, the pore structure of the negative electrode active material can be further optimized, the non-Faraday reaction of the negative electrode sheet can be enhanced, and the overall performance of the secondary battery can be further improved.
[0042] In some embodiments, the pore volume of the negative electrode active material is α cm 3 / g, and the numerical range of α is 0.001≦α≦0.5, specifically, α may be any one of 0.001, 0.005, 0.01, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, or any two of them. When the pore volume of the negative electrode active material satisfies the above range, the pore structure of the negative electrode active material granules is large, which not only improves the contact area between the electrode and the electrolyte, but also shortens the transport path of lithium ions, realizes rapid impregnation of the electrolyte, provides a smooth charge transport path at the solid-liquid interface, reduces the diffusion barrier, and allows lithium ions to be rapidly absorbed and released on the surface of the negative electrode material, accelerating the reaction kinetics.
[0043] In some embodiments, the pore volume of the negative electrode active material is α cm 3 / g, and the numerical range of α is 0.005≦α≦0.45.
[0044] In some embodiments, the pore volume of the negative electrode active material is α cm 3 / g, and the numerical range of α is 0.008≦α≦0.42.
[0045] In some embodiments, the pore volume of the negative electrode active material is α cm 3 / g, and the numerical range of α is 0.01≦α≦0.38. When the pore volume of the negative electrode active material satisfies the above range, the pore structure of the negative electrode active material can be further optimized, and the overall performance of the secondary battery can be further improved.
[0046] In some embodiments, the pore volume of the negative electrode active material is α cm 3 / g, and the numerical range of α is 0.05≦α≦0.38.
[0047] In some embodiments, the pore volume of the negative electrode active material is α cm 3 / g, and the numerical range of α is 0.08≦α≦0.38.
[0048] In some embodiments, the pore volume of the negative electrode active material is α cm 3 / g, and the numerical range of α is 0.1≦α≦0.38.
[0049] In some embodiments, the pore volume of the negative electrode active material is α cm 3 / g, and the numerical range of α is 0.12≦α≦0.38. When the pore volume α of the negative electrode active material satisfies the above range, the active sites on the surface of the negative electrode sheet are increased, which is favorable for the lithium ions to exchange charges on the surface of the negative electrode active material, thereby improving the multiplication performance of the lithium ion battery and favorable for the lithium ions to diffuse into the inside of the negative electrode active material, thereby improving the solid-state conductive ability of the lithium ions, reducing the resistance of the secondary battery, and extending the life of the secondary battery.
[0050] In some embodiments, the powder resistivity of the negative electrode active material at 20 KN is R Ω·cm, and in some embodiments, the relationship between R and Cdl is 0.01≦10R / Cdl≦5. Specifically, the numerical range of 10R / Cdl may be any one of 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, and 5.0, or a range consisting of any two numbers therein. When the negative electrode sheet satisfies the above relationship, the electronic conductivity of the negative electrode active material is relatively high, the interfacial resistance between the electrolyte and the negative electrode active material is low, and the polarization of the secondary battery is small, thereby improving the cycle performance and the power supply performance of the secondary battery.
[0051] In some embodiments, the powder resistivity of the negative electrode active material at 20 KN is R Ω·cm, and in some embodiments, the relationship between R and Cdl is 0.12≦10R / Cdl≦4.3.
[0052] In some embodiments, the powder resistivity of the negative electrode active material at 20 KN is R Ω·cm, and in some embodiments, the relationship between R and Cdl is 0.18≦10R / Cdl≦3.9.
[0053] In some embodiments, the powder resistivity of the negative active material at 20 KN is R Ω·cm, and 0.002≦R≦2. Specifically, the numerical range of R may be any one of 0.002, 0.005, 0.01, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, 1.5, and 2.0, or any two of them. When the powder resistivity of the negative active material at 20 KN satisfies the above range, the negative sheet can have better conductive performance, which affects the performance of the negative sheet to a certain extent and further improves the overall performance of the secondary battery.
[0054] In some embodiments, the powder resistivity of the negative electrode active material at 20 KN is R Ω·cm, and 0.008≦R≦1.8.
[0055] In some embodiments, the powder resistivity of the negative electrode active material at 20 KN is R Ω·cm, where 0.011≦R≦1.4.
[0056] In some embodiments, the powder resistivity of the negative electrode active material at 20 KN is R Ω·cm, where 0.021≦R≦1.4.
[0057] The powder resistivity R of the negative electrode active material can be measured by the four-probe method of GB / T 39978-2021.
[0058] In some embodiments, the particle size distribution of the negative electrode active material is A, and in some embodiments, 0.5≦A≦2.5. Specifically, A may be in the range of 0.5, 0.8, 1.0, 1.2, 1.5, 1.8, 2.0, 2.3, 2.5, or any two of the numbers therein.
[0059] In some embodiments, the particle size distribution of the negative electrode active material is A, and in some embodiments, 0.7≦A≦2.
[0060] In some embodiments, the particle size distribution of the negative electrode active material is A, and in some embodiments, 0.7≦A≦1.9. The particle size distribution value is (D99−D10) / D50, where D99 represents the particle size corresponding to a cumulative particle size volume distribution percentage of the active material granules of 99%, D10 represents the particle size corresponding to a cumulative particle size volume distribution percentage of the active material granules of 10%, and D50 represents the particle size corresponding to a cumulative particle size volume distribution percentage of the active material granules of 50%. The particle size distribution is used to characterize the dispersion degree of the content of various particle size components, the smaller the particle size distribution, the more concentrated the particle size distribution, the better the dispersion effect of the powder material during the stirring process, the less likely the slurry to settle, and the uniformity and stability of the obtained slurry are both relatively good, so that the uniformity of the coating weight of the electrode sheet can be effectively controlled to enhance the stability of the electrode sheet, and thus the purpose of controlling the non-Faraday reaction process can be achieved, and the transport efficiency of lithium ions between the positive electrode sheet and the negative electrode sheet can be improved, thereby improving the multiplication performance of the secondary battery. The particle size distribution being too large indicates that the particle size distribution is too wide, and the small granular negative electrode active material is easily absorbed between the large granular negative electrode active material, so that the granular space between the negative electrode active material becomes too dense, which affects the absorption and release of lithium ions, and the cycle performance and dynamic performance of the negative electrode sheet are rather reduced, and the slurry is also difficult to manufacture.
[0061] When the particle size distribution A of the negative electrode active material in the negative electrode sheet satisfies the above range, the stability of the negative electrode sheet is enhanced, and the multiplication performance of the secondary battery is improved.
[0062] The particle size distribution A of the negative electrode active material can be calculated by measuring D99, D10, and D50 of the negative electrode active material using a laser granulometer. Specifically, the method of obtaining the negative electrode active material from the negative electrode sheet may be as follows. The secondary battery is discharged to the lower limit voltage at a constant current of 0.04C, disassembled to obtain a negative electrode sheet, and the negative electrode sheet is immersed and washed in a DMC (dimethyl carbonate) solution, washed several times with deionized water, the upper layer solution is removed, the lower layer solution is left to dry, and heat treated in an argon atmosphere at 800°C for 2 hours to obtain the above test sample.
[0063] The thickness of the negative electrode active material layer is C μm, and in some embodiments, the numerical range of C is 99≦C≦160, and specifically, the numerical range of C may be any of 99, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, 150, 155, 160, or any two of them. When the thickness of the negative electrode active material layer is in the above range and the curvature and length of the lithium ion and electron transfer path are small, the diffusion ability of the lithium ions and electrons in the negative electrode sheet is strong, so that the multiplication performance of the secondary battery can be further improved. In addition, the thickness of the negative electrode active material layer may also affect the binding force between the negative electrode active material layer and the negative electrode current collector, and therefore affect the performance of the negative electrode sheet.
[0064] In some embodiments, the negative electrode active material layer has a thickness of C μm, where C is in the range of 116≦C≦155.
[0065] In some embodiments, the thickness of the negative electrode active material layer is C μm, and C is in the range of 116≦C≦149. When the thickness C of the negative electrode active material layer satisfies the above range, the diffusion ability of lithium ions in the negative electrode active material layer is enhanced, and the secondary battery has relatively high fold performance and energy density.
[0066] In some embodiments, the negative electrode active material layer is disposed on one surface of the negative electrode current collector.
[0067] In some embodiments, the negative electrode active material layers are disposed on both surfaces of a negative electrode current collector.
[0068] When the negative electrode sheet has both an active material layer region on one side and an active material layer region on both sides, the thickness of the negative electrode sheet is the thickness of the negative electrode active material layer region on both sides. The thickness of the negative electrode active material layer can be measured with a vernier caliper.
[0069] In some embodiments, a first coating layer is disposed on a surface of the negative electrode active material, and the first coating layer has a thickness H1 nm. In some embodiments, the relationship between H1 and Cdl is 10≦Cdl×H1≦250. Specifically, the numerical range of Cdl×H1 may be any one of 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, and 250, or any two of the ranges.
[0070] In some embodiments, a first coating layer is disposed on a surface of the negative electrode active material, and the first coating layer has a thickness H1 nm, and in some embodiments, the relationship between H1 and Cdl is 20≦Cdl×H1≦230.
[0071] In some embodiments, a first coating layer is disposed on a surface of the negative electrode active material, and the first coating layer has a thickness H1 nm, and in some embodiments, the relationship between H1 and Cdl is 31≦Cdl×H1≦210.
[0072] In some embodiments, the thickness of the first coating layer is H1 nm, and 5≦H1≦200. Specifically, the numerical range of H1 may be any one of 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, and 200, or a range consisting of any two of the numbers therein.
[0073] In some embodiments, the first coating layer has a thickness H1 nm, where 11≦H1≦180.
[0074] In some embodiments, the first coating layer has a thickness H1 nm, where 21≦H1≦165.
[0075] In some embodiments, the first coating layer is a carbon coating layer, which is formed by a heat treatment process such as sintering any one of organic resin, asphalt, citric acid, glucose, and hard carbon.
[0076] The secondary battery is manufactured through a heat treatment process, during which the negative active material is subjected to different degrees of centrifugal pressure, and due to the action of external forces in different directions, internal defects appear in the negative active material, for example, the inside is relatively loose and prone to collapse, and the first coating layer is used to uniformly coat the granules of the negative active material, and the obtained negative active material has relatively strong structural stability, and the external coating structure formed by the first coating layer can eliminate the internal defects, improve the diffusion performance of lithium ions therein, and reduce the expansion of the material, which is favorable to improving the electrochemical performance such as the fold performance and cycle of the secondary battery. In addition, the carbon coating layer can provide more active sites, which reduces the transport resistance of lithium ions on the surface and transport path of the negative active material, which is favorable to the absorption and release of lithium ions, and reduces the resistance of the negative active material, improving the liquid absorption performance, and thereby improving the fold performance.
[0077] In some embodiments, referring to FIG. 1, a method for testing the non-Faraday capacitance value Cdl of a negative electrode sheet includes the following steps:
[0078] In S1, the non-Faraday potential range confirmation step, the negative electrode sheet is assembled into a half cell (abbreviated as button cell) and a cyclic voltammogram (CV) test is performed, where the voltage range is 0.005V to 3.0V, the scan rate is 0.1mV / s to 1mV / s, and the non-Faraday potential range is the flat section of the curve, i.e., the range of 2V to 3V.
[0079] In step S2, the non-Faraday range cathodic scanning step, a potential range is selected from the potential range of 2V to 3V confirmed in step S1 to perform a linear scan voltammogram (LSV) test, the scanning direction is from high potential to low potential, and a voltage-current curve is collected, where the selected potential range is 2.6V to 2.7V, and the scanning rate is 0.05mV / s to 5mV / s.
[0080] Furthermore, select the median U V in the potential range of 2.6 V to 2.7 V at a scan rate of 0.1 mV / s, and obtain the corresponding current value of U = 2.65. Select the current values corresponding to the median U at each different scan rate within the scan rate range of 0.055 mV / s to 5 mV / s, and obtain a scatter diagram of scan rate vs. current density.
[0081] In step S3, the non-Faraday capacitance calculation step, a linear function is obtained by fitting based on the scatter diagram of the scanning speed-current density collected in step S2, and the slope K of the linear function is the non-Faraday capacitance value Cdl of the negative electrode sheet in the cathode scanning direction.
[0082] The button battery is assembled as follows. The negative electrode sheet is dried, cut into small circular sheets, weighed, and then transferred to a vacuum oven, dried at 100°C for 8 hours, and then transferred to a glove box filled with argon gas again to assemble the half cell. The assembly method is a common assembly method in the art. The non-Faraday potential range is confirmed using the cyclic Voltammogram curve, the current value is measured using the linear scanning Voltammogram curve in the potential range, and the non-Faraday capacity value Cdl is calculated by fitting.
[0083] In some embodiments, the negative current collector includes, but is not limited to, a metal foil, a metal cylinder, a roll of metal tape, a metal sheet, a metal thin film, a metal sheet mesh, a stamping metal, a metal foam, and the like. In some embodiments, the negative current collector is a metal foil. In some embodiments, the negative current collector is an aluminum foil or a copper foil. As used herein, the term "copper foil" includes copper alloy foil.
[0084] In some embodiments, the negative electrode current collector is a composite current collector, and the composite current collector comprises a conductive resin.
[0085] In some embodiments, the negative electrode current collector is a copper vapor deposited polypropylene film.
[0086] In some embodiments, the negative electrode active material layer includes a negative electrode active material, a conductive agent, an adhesive, and a dispersant.
[0087] In some embodiments, the negative electrode active material comprises one or more of natural graphite, synthetic graphite, hard carbon, soft carbon, and mesocarbon microspheres.
[0088] In some embodiments, a method for producing an anode active material includes the following steps.
[0089] The raw materials are pretreated by crushing and premixing, and the particle size after crushing is 8μm~10μm. The crushed material is subjected to high-temperature graphitization treatment under a protective atmosphere, the temperature is 2800℃~3000℃, and the temperature is kept at 3000℃ for 30h~60h, and the protective atmosphere is inert gas. After that, the product is polished and shaped for 4h~12h to smooth and flatten the surface of the product granules, and a negative electrode active material with a particle size D50 of 10μm~20μm and a crystal grain size XS nm of 0.01nm~6nm is obtained.
[0090] In some embodiments, the conductive agent comprises one or more of carbon black, graphite, carbon fiber, carbon nanotubes, or graphene.
[0091] The adhesive improves adhesion between the negative electrode active materials. There are no particular limitations on the type of adhesive, and any material may be used as long as it is stable against the electrolyte and the solvent used in the manufacture of the electrode.
[0092] In some embodiments, the adhesive comprises sodium carboxymethyl cellulose and styrene butadiene rubber.
[0093] In some embodiments, the adhesive comprises sodium carboxymethyl cellulose, oxidized starch, and styrene butadiene rubber.
[0094] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, the positive electrode active material layer including a positive electrode active material.
[0095] The positive electrode sheet is a single-sided sheet or a double-sided sheet, and when the positive electrode sheet is a single-sided sheet, the positive electrode active material layer is disposed on one surface of the positive electrode current collector, and when the positive electrode sheet is a double-sided sheet, the positive electrode active material layer is disposed on both surfaces of the positive electrode current collector. The positive electrode sheet may simultaneously have a positive electrode active material layer region on one side and a positive electrode active material layer region on both sides.
[0096] When a positive electrode sheet has a positive electrode active material layer region on one side and a positive electrode active material layer region on both sides at the same time, the thickness of the positive electrode sheet is the thickness of the positive electrode active material layer regions on both sides.
[0097] In some embodiments, the particle size distribution of the positive electrode active material is B, and 1.0≦B≦5.0. Specifically, the numerical range of B may be any one of 1.0, 1.2, 1.5, 1.8, 2.0, 2.3, 2.5, 2.8, 3.0, 3.2, 3.5, 3.8, 4.0, 4.2, 4.5, 4.8, and 5.0, or a range consisting of any two numbers therein.
[0098] In some embodiments, the positive electrode active material has a particle size distribution B, where 1.3≦B≦4.5.
[0099] In some embodiments, the positive electrode active material has a particle size distribution B, where 1.9≦B≦3.9.
[0100] In some embodiments, the positive electrode active material has a particle size distribution B, where 2.1≦B≦3.9.
[0101] The particle size distribution value is (D99-D10) / D50, where D99 is the particle size corresponding to the cumulative particle size volume distribution percentage of the active material granules being 99%, D10 is the particle size corresponding to the cumulative particle size volume distribution percentage of the active material granules being 10%, and D50 is the particle size corresponding to the cumulative particle size volume distribution percentage of the active material granules being 50%. The particle size distribution is used to characterize the dispersion degree of the content of various particle size components, and the smaller the particle size distribution, the more concentrated the particle size distribution is. The dispersion effect of the powder material during the stirring process is good, the slurry is not easily settled, and the uniformity and stability of the obtained slurry are both relatively good, so that the uniformity of the coating weight of the positive electrode sheet can be effectively controlled, thereby enhancing the stability of the positive electrode sheet, and thus achieving the purpose of controlling the non-Faraday reaction process, improving the transport efficiency of lithium ions between the positive electrode sheet and the negative electrode sheet, and improving the multiplication performance of the secondary battery. Too large a particle size distribution indicates that the particle size distribution is too broad, and small granules of the positive electrode active material are easily absorbed between large granules of the positive electrode active material, so that the spaces between the granules of the positive electrode active material become too dense, which affects the absorption and release of lithium ions and rather reduces the cycle performance and kinetic performance of the positive electrode sheet, and also makes it difficult to prepare a slurry.
[0102] When the particle size distribution A of the positive electrode active material in the positive electrode sheet satisfies the above range, the stability of the positive electrode sheet is enhanced, and the multiplying performance of the secondary battery is improved.
[0103] The relationship between the particle size distribution A of the negative electrode active material and the particle size distribution B of the positive electrode active material is 0.1≦A / B≦2.5, and specifically, the numerical range of the ratio of A / B may be any of 0.1, 0.2, 0.3, 0.5, 0.7, 0.8, 1.0, 1.2, 1.5, 1.8, 2.0, 2.3, 2.5, or any two of them. When the particle size distribution A of the negative electrode active material and the particle size distribution B of the positive electrode active material satisfy the above range, a negative electrode sheet and a positive electrode sheet with a high tap density are obtained, and both the positive electrode sheet and the negative electrode sheet have high electron and lithium ion transport performance, and the transport efficiency of electrons and lithium ions in the positive electrode sheet and the negative electrode sheet are better matched, and the secondary battery has a high multiplication performance and a relatively high charge and discharge performance, and at the same time has a relatively high energy density.
[0104] In some embodiments, the relationship between particle size distribution A of the negative electrode active material and particle size distribution B of the positive electrode active material is 0.3≦A / B≦2.2.
[0105] In some embodiments, the relationship between particle size distribution A of the negative electrode active material and particle size distribution B of the positive electrode active material is 0.5≦A / B≦1.9.
[0106] The particle size distribution B of the positive electrode active material in the positive electrode sheet may be obtained by directly calculating the particle size of the positive electrode active material using a laser granulometer. Alternatively, the secondary battery is discharged at a constant current of 0.04C to the lower limit voltage, disassembled to obtain a positive electrode sheet, immersed in a DMC (dimethyl carbonate) solution and washed, and the positive electrode sheet is baked in a muffle furnace at 400°C for 5h to remove the powder, washed with deionized water 2-3 times, and left to stand after each washing to remove the supernatant liquid, and the lower layer solution is left to stand and dried to obtain a test sample.
[0107] In some embodiments, the thickness of the positive electrode active material layer is D μm, and D is in the range of 80≦D≦130. Specifically, D may be in the range of 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, or 130, or any two of these numbers. When a positive electrode active material layer is disposed on both sides of the positive electrode current collector, D μm is the total thickness of the two positive electrode active material layers.
[0108] When the thickness of the positive electrode active material layer satisfies the above range, the tortuosity and length of the lithium ion and electron transfer path are within an appropriate range, the lithium ions and electrons have excellent diffusion ability in the positive electrode sheet, the secondary battery has good multiplication performance, and the specific capacity and energy density of the secondary battery can be guaranteed within an appropriate range. In addition, the binding force between the positive electrode active material layer and the positive electrode current collector can be kept within an appropriate range, and the positive electrode sheet performance can be fully exhibited.
[0109] In some embodiments, the thickness of the positive electrode active material layer is D μm, and D is in the range of 91≦D≦125. When the thickness D of the positive electrode active material layer satisfies the above range, the diffusion ability of lithium ions in the positive electrode active material layer is enhanced, and the secondary battery has a relatively high multiplication performance and energy density.
[0110] In some embodiments, the positive electrode active material layer has a thickness of D μm, where D is in the range of 101≦D≦125.
[0111] In some embodiments, the relationship between the thickness C μm of the negative electrode active material layer and the thickness D μm of the positive electrode active material layer is 0.1≦1-(D / C)≦0.5, and specifically, the numerical range of 1-(D / C) may be any of 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, and 0.5, or any two of them. When the thickness C of the negative electrode active material layer and the thickness D of the positive electrode active material layer satisfy the above range, the electrolyte can be sufficiently diffused in the positive electrode sheet and the negative electrode sheet, the ohmic resistance of the electrode sheet can be reduced, lithium deposition on the negative electrode sheet can be avoided, and the dynamic performance of the secondary battery can be improved while ensuring high energy density.
[0112] In some embodiments, the relationship between the thickness C μm of the negative electrode active material layer and the thickness D μm of the positive electrode active material layer is 0.13≦1−(D / C)≦0.45.
[0113] In some embodiments, the relationship between the thickness C μm of the negative electrode active material layer and the thickness D μm of the positive electrode active material layer is 0.17≦1−(D / C)≦0.40.
[0114] A second coating layer is disposed on the surface of the positive electrode active material, and the second coating layer has a thickness H2 nm, and in some embodiments, 5≦H2≦60. Specifically, H2 may be in the range of 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, or 60, or any two of the ranges.
[0115] In some embodiments, the second coating layer comprises a coating element, the coating element including at least one of F, Al, Mg, Ti, and Zr.
[0116] In some embodiments, the second coating layer is selected from an organic polymer, an inorganic metal fluoride, an oxide, or a lithiate.
[0117] By performing coating modification on the positive electrode active material, it is possible to suppress the occurrence of side reactions between the positive electrode active material and the electrolyte, prevent chemical erosion of the electrolyte, reduce the elution of transition metals, improve the structural stability of the positive electrode active material layer, improve the electrical conductivity of the positive electrode active material layer, and further improve the cycle stability and power supply performance of the secondary battery.
[0118] The positive electrode active material layer may be one or more layers. Each layer in the multi-layer positive electrode active material may contain the same or different positive electrode active material. The positive electrode active material is any material capable of reversibly absorbing and releasing metal ions, such as lithium ions.
[0119] In some embodiments, the active cathode material can include a ternary material, which can include lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide.
[0120] In some embodiments, the cathode active material comprises lithium nickel cobalt manganese oxide, in which the molar ratio of elemental nickel to elemental cobalt to elemental manganese is 1, and the content of elemental nickel is 0.5 or more.
[0121] In some embodiments, the cathode active material comprises lithium nickel cobalt manganese oxide, the molar ratio of elemental nickel to elemental cobalt to elemental manganese being 1, in which the content of elemental nickel is less than or equal to 0.85.
[0122] In some embodiments, the positive electrode active material includes a doping element and / or a coating element.
[0123] The positive electrode active material layer further includes a positive electrode conductive agent and a positive electrode adhesive.
[0124] The type of the positive electrode conductive agent is not particularly limited, and any known conductive agent can be used. The positive electrode conductive agent includes, but is not limited to, natural graphite, artificial graphite, acetylene black, carbon materials such as needle coke, carbon nanotubes, graphene, etc. The positive electrode conductive agent may be used alone or in any combination.
[0125] The type of solvent for forming the positive electrode slurry is not limited, and any solvent capable of dissolving or dispersing the positive electrode active material, the positive electrode conductive agent, and the positive electrode adhesive may be used. Examples of the solvent for forming the positive electrode slurry include aqueous and organic solvents. The type of the positive electrode current collector is not particularly limited, and any known material suitable for the positive electrode current collector may be used. Examples of the positive electrode current collector include, but are not limited to, metal materials such as aluminum, stainless steel, nickel plating, titanium, and tantalum, carbon materials such as carbon cloth and carbon paper, and composite materials consisting of polymers and metal layers. In some embodiments, the positive electrode current collector is a metal material. In some embodiments, the positive electrode current collector is aluminum.
[0126] The form of the positive electrode current collector is not particularly limited. In some embodiments, the positive electrode current collector is a metal foil. In some embodiments, the thickness of the metal foil is greater than 1 μm, greater than 3 μm, or greater than 5 μm. In some embodiments, the thickness of the metal foil is less than 1 mm, less than 50 μm, or less than 20 μm. In some embodiments, the thickness of the metal foil is in the range consisting of any two of the above numbers.
[0127] The electrolyte includes a lithium salt, an organic solvent, and an additive.
[0128] In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate, lithium organoborate, lithium perchlorate, and sulfonimide type lithium salt. The content of the lithium salt is not particularly limited as long as it does not impair the effect of the present application.
[0129] In some embodiments, the organic solvent comprises a cyclic carbonate and a linear carbonate.
[0130] Specifically, the organic solvent is a mixed solvent containing one or more of ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), propylene carbonate (PC), and methyl ethyl carbonate (EMC).
[0131] In some embodiments, the additive comprises at least one of vinylene carbonate, 1,3-propanesulfonate, lithium difluorophosphate, fluoroethylene carbonate (FEC), lithium difluorooxalate borate, tripropynyl phosphate, triallyl phosphate, and triallyl isocyanurate.
[0132] In order to prevent short circuits, a separator is usually disposed between the positive and negative electrodes, and in this case, the electrolyte of the present invention is usually used by permeating the separator.
[0133] In addition, the present embodiment further provides a battery pack, which includes a secondary battery. Representative applications of the battery pack include, but are not limited to, electric toys, electric tools, battery vehicles, electric vehicles, energy storage devices, ships, spacecraft, etc.
[0134] Hereinafter, the method for producing a secondary battery provided by the present invention will be described based on specific examples.
[0135] Example 1
[0136] The positive electrode sheet was produced as follows.
[0137] Ternary cathode active material LiNi 0.8 Co 0.1 Mn 0.1O2 (NCM811) is added to the aluminum chloride solution, ammonia water is added to maintain the pH stability of the solution, and after hydrolysis for 8h, the solution is filtered, repeatedly washed with deionized water and alcohol, dried, and then heat-treated in a horizontal kettle at 600℃ for 5h to obtain a positive electrode active material coated with aluminum trioxide, the thickness H2 of which is 30nm. The coated ternary positive electrode active material NCM811 is baked at 85℃ for 8h, and then thoroughly stirred and mixed with conductive carbon black Super P and adhesive polyvinylidene fluoride (PVDF) in a weight ratio of 96:2:2, N-methylpyrrolidone (NMP) is added and high-speed dispersion is performed for 4h, scraping is performed, bottom rotation is performed, NMP is added again to adjust the viscosity of the slurry, defoaming treatment is performed, and the final viscosity of the slurry is in the range of 2500~5000mPa.s. The produced positive electrode slurry is uniformly coated on both sides of an aluminum foil positive electrode current collector, then baked and dried at 120°C, rolled and cut to obtain a positive electrode sheet, and the thickness D μm of the positive electrode active material layer is 90 μm.
[0138] The negative electrode sheet was produced as follows.
[0139] The manufacturing steps of the negative electrode active material include the following: Petroleum coke is crushed by abrasive rolls and pre-mixed, and the particle size after crushing is 9μm. The crushed product is subjected to high-temperature graphitization treatment at 2900℃ in a protective atmosphere, and is kept at 3000℃ for 48h in an argon protective atmosphere. The product is then polished and shaped in a continuous shaping system for 8h to smooth and flatten the surface of the product granules, and artificial graphite is obtained as the negative electrode active material with a particle size D50 of 13μm and a grain size XS of 0.5nm.
[0140] The negative electrode active material, artificial graphite, and the first coating layer asphalt are placed in a thermal reactor, stirred and mixed for 6 hours, and then heat-treated at 1200°C for 2 hours under the protection of inert gas to obtain a negative electrode active material with a first coating layer, the thickness H1 of which is 77 nm. The negative electrode active material, conductive carbon black Super P, adhesive sodium carboxymethylcellulose, starch oxide, and styrene butadiene rubber are mixed in a weight ratio of 96.5:1.2:1.1:0.2:1.0 to prepare a negative electrode slurry. First, graphite, carbon black, and 80% sodium carboxymethylcellulose are mixed at low speed to be uniformly mixed, then the remaining 20% sodium carboxymethylcellulose, 50% oxidized starch, and deionized water are added and stirred at high speed for 2h, then 50% oxidized starch and styrene butadiene rubber are added and stirred at low speed, and then the viscosity of the slurry is controlled within the range of 2500mPa.s to 4000mPa.s, and the slurry is passed through a 200 mesh sieve to produce a negative electrode slurry. The produced negative electrode slurry is uniformly coated on one or both sides of the copper foil of the negative electrode current collector, and then the negative electrode is baked and dried in five stages at 90°C to 110°C, rolled, and cut to obtain a negative electrode sheet, and the thickness C μm of the negative electrode active material layer is set to 110 μm.
[0141] The electrolyte was prepared as follows.
[0142] Ethylene carbonate (EC), methyl ethyl carbonate (EMC), and diethyl carbonate (EDC) are mixed in a volume ratio of 1:1:1, and then 1 mol / L of LiPF6 is added and mixed uniformly to prepare an electrolyte.
[0143] The secondary battery is manufactured as follows.
[0144] The negative and positive electrode sheets prepared by the above steps are dried, then wound together with the separator using a winding machine to produce an electric core, the positive electrode aluminum tab and the negative electrode copper-nickel plated tab are welded to the electric core, and the welded electric core is packaged in a pre-punched aluminum plastic film, and the separator is a PP film, and the secondary battery is manufactured through injection, chemical formation and volume control.
[0145] The non-Faraday capacitance Cdl test is as follows.
[0146] Step 1: The secondary battery prepared in Example 1 is disassembled in a glove box, and a sheet in the negative electrode overhang region is obtained, soaked in a dimethyl carbonate (DMC) solution, cut, and then assembled into a button half-cell using the sheet and a metallic lithium sheet, or cut the negative electrode sheet not assembled into a battery, and then assembled into a button half-cell using the sheet and a metallic lithium piece.
[0147] Step 2, perform a CV test on the button half-cell in the voltage range of 0.005 V to 3.0 V, with a scan rate of 0.1 mV / s, ensuring that the non-Faraday potential range is 2.5 V to 2.6 V.
[0148] Step 3: Next, perform LSV test from 2.6V to 2.5V, with the scan rates of 0.1mV / s, 0.2mV / s, 0.5mV / s, 1mV / s, and 2mV / s, respectively, and select the middle value of the potential range, 2.55V, to obtain the corresponding current values of 1.96E-05A, 1.83E-05A, 1.71E-05A, 1.58E-05A, and 1.36E-05A.
[0149] Step 4: Based on the scanning speed and current value obtained in step 3, a scatter diagram of scanning speed-current density shown in FIG. 1 is made and fitted to obtain a linear function, the gradient of which is −2.86E-06, that is, the non-Faraday capacitance value Cdl of the negative electrode sheet in the cathode scanning direction is 2.86 nF.
[0150] The non-Faraday reaction range curve of the linear scan voltammogram (LSV) at different scan rates, i.e., the current exhibits a linear change with the change in scan rate, can be used to evaluate the non-Faraday capacitance value (Cdl), which plays an important role in characterizing the number of active sites. In a certain range, increasing Cdl increases the number of electrochemically active sites, which is favorable for the contact between the negative electrode active material and the electrolyte, accelerates the rate of ion-electron conduction, reduces the resistance of charge transport, and effectively improves the charge multiplier performance of the secondary battery.
[0151] Here, the negative electrode sheet overhang region refers to the portion of the negative electrode sheet that protrudes from the positive electrode sheet in the longitudinal and transverse directions.
[0152] Examples 2 to 16
[0153] A secondary battery is manufactured using the method described in Example 1, and the particle size after crushing the petroleum coke, the graphitization temperature, the heating temperature, the warming time, and the grinding and shaping time are controlled to make the characteristics of the negative electrode sheet and the negative electrode active material as shown in Figures 2 to 5.
[0154] Examples 17 to 30
[0155] A secondary battery is manufactured using the method described in Example 1, and the parameters of the positive electrode sheet and the negative electrode sheet are set to the values shown in Figures 2 to 5 by controlling the particle size after crushing the petroleum coke, the graphitization temperature, the heating temperature, the heat retention time, and the polishing and shaping time.
[0156] Comparative Examples 1 to 4
[0157] A secondary battery was manufactured using the method described in Example 1, with the differences shown in FIGS.
[0158] The performance test process of the manufactured secondary battery is as follows.
[0159] The grain size of the negative electrode active material is tested (XS nm).
[0160] X-ray diffraction measurements using CuKα radiation were performed on the negative electrode active materials produced in the examples and comparative examples, and the (002) peaks at diffraction angles 2θ in the range of 25° to 27° belonging to the negative electrode active materials were analyzed, and the crystal grain sizes of the negative electrode active materials were calculated using the Schrödinger equation. The test results are shown in Figures 2 and 3.
[0161] Pore volume of negative electrode active material α cm 3 / g is tested.
[0162] The shapes of the negative electrode active materials prepared in the Examples and Comparative Examples were observed using a scanning electron microscope (SEM). The pore volumes of the negative active materials prepared in the Examples and Comparative Examples were measured using a porosity measuring analyzer (Belsorp-II mini, Bell Japan Inc.) by a BET 6-point method based on a nitrogen gas adsorption flow method, and the test results are shown in Figures 2 and 3.
[0163] Test the powder resistivity R Ω·cm of the negative electrode active material.
[0164] The negative active material powders prepared in the examples and comparative examples were dried and weighed out to measure the resistivity of the powder using a powder resistivity tester, model numbers of which are Suzhou Jingge ST2722 and Sansi UTM7305. The dried powder sample was placed in the mold / sample chamber of the resistivity tester, with the sample chamber having a depth of 20 mm and a cross-sectional area of 1 cm. 2 Then, the applied pressure was gradually increased, and data was manually collected and the test results of the corresponding powder resistivity under different pressure points were recorded, and the test results are shown in Figures 2 to 3.
[0165] The cycle performance test of the secondary battery is as follows.
[0166] The secondary battery is charged and discharged at 25° C. Specifically, it is charged at a constant current of 1C, left to stand for 30 minutes, and discharged at a constant current of 1C, the first discharge capacity is recorded, the battery is cycled through 1000 1C / 1C charge and discharge cycles, the 1000th discharge capacity of the secondary battery is recorded, and the 1000th discharge capacity of the battery is divided by the first discharge capacity of the battery to obtain the capacity retention rate of the secondary battery after cycling through 1000 charge and discharge cycles, and the test results are shown in FIG. 4 to FIG. 5.
[0167] The multiplication performance test for secondary batteries is as follows.
[0168] The secondary battery was subjected to high-power charging at 25° C. Specifically, it was discharged at a constant current of 1C, left to stand for 10 minutes, and charged at a constant current of 4C, the first discharge capacity was recorded, and the charge capacity was divided by the first discharge capacity of the lithium-ion battery charged and discharged at 1C / 1C at 25° C. to obtain the 4C power performance of the secondary battery, and the test results are shown in FIG. 4 and FIG. 5.
[0169] To facilitate understanding of the present application, the present application lists data on Examples 1 to 30 and Comparative Examples 1 to 4 as shown in Figures 2 to 5. Those skilled in the art should understand that these examples are merely to aid in understanding of the present application and are not intended to limit the present application.
[0170] The non-Faraday capacity value Cdl of the negative electrode sheet of the secondary battery affects the number of electrochemically active points and the contact between the negative electrode active material and the electrolyte, and the non-Faraday capacity value Cdl of the negative electrode sheet affects the conduction speed of ions and electrons and the charge transport resistance, so that it can effectively affect the multiplication performance of the secondary battery. The factors that affect the cycle performance under high voltage and high temperature and the capacity performance at high current of the crystal grain size XS of the negative electrode active material are mainly that the crystal grain size of the negative electrode active material affects the actual contact area between the electrode and the electrolyte, affects the distance of ion and electron transport and the number of electrochemically active points, and thus affects the non-Faraday reaction strength and charge transfer resistance of the negative electrode sheet, and affects the multiplication performance of the secondary battery.
[0171] Therefore, as shown in FIGS. 2 to 5, when comparing the secondary batteries provided by Examples 1 to 16 with the secondary battery provided by Comparative Example 1, the non-Faraday capacitance value of the negative electrode sheet is 0.05 nF to 10 nF, and the non-Faraday capacitance value is within the range of 0.05 nF to 10 nF.
number
[0172] Referring to Comparative Example 1, the non-Faraday capacity value Cdl of the secondary battery provided by Comparative Example 1 is significantly different from that of the crystal grain size XS.
number
number
[0173] Comparing Example 11 and Example 16, the non-Faraday capacitance value of the negative electrode sheet is 0.05 nF to 10 nF,
number
[0174] With reference to Examples 5 and 10, the secondary battery manufactured in Example 5 has a Cdl+10×α value of 9.5, which exceeds the upper limit of 0.5≦Cdl+10×α≦8 defined in the present application, and the cycle performance at 25° C. of the secondary battery manufactured in Example 5 is 87% and the 4C multiplier performance is 85%. The secondary battery manufactured in Example 10 has a Cdl+10×α value of 5.9, which is within the range of 0.5≦Cdl+10×α≦8 defined in the present application, and the cycle performance at 25° C. of the secondary battery manufactured in Example 10 is 90% and the 4C multiplier performance is 89%.
[0175] Therefore, referring to FIGS. 4 and 5, the secondary batteries manufactured in Examples 21 to 23 and Example 21 have B / A=2.5, which is the upper limit value. This indicates that the particle size distribution of the positive electrode active material and the particle size distribution of the negative electrode active material in the secondary batteries are significantly different. The particle size distribution is wide, and small granules of the positive electrode active material are easily absorbed between large granules of the positive electrode active material. As a result, the granules of the active material become too dense, which affects the absorption and release of lithium ions and affects the cycle performance and kinetic performance of the secondary battery. The cycle performance and 4C multiplier performance at 25° C. of the secondary batteries manufactured in Examples 22 and 23 are superior to those of Example 21.
[0176] In addition, when the thickness C of the negative electrode active material layer and the thickness D of the positive electrode active material layer are within the range of 0.1≦1-(D / C)≦0.5, the electrolyte can sufficiently diffuse in the positive and negative electrode sheets, thereby reducing the ohmic resistance of the electrode sheets, preventing lithium deposition on the negative electrode sheet, and improving the kinetic performance while ensuring a high energy density.
[0177] 4-5, the thickness C of the negative electrode active material layer of the secondary battery manufactured in Example 24 is 160 μm, which is the upper limit of the range C defined by the present application, and the thickness D of the positive electrode active material layer is 80 μm, which is the lower limit of the range D defined by the present application, so 1-(D / C)=0.5, and the thickness C of the negative electrode active material layer is relatively thick, which increases the curvature and length of the lithium ion and electron transfer path, reduces the diffusion ability of lithium ions and electrons in the positive electrode sheet, and reduces the multiplication performance of the negative electrode sheet. When the active material is bound to at least one surface of the current collector by a binder, the thickness of the active material layer that is too thick reduces the binding force between the active material layer and the current collector, affecting the performance of the electrode sheet, so that the cycle performance at 25 ° C of the secondary battery manufactured in Example 24 is 84%, and the 4C multiplication performance is 84%.
[0178] With reference to Example 15 and Example 1, in Example 15, the surface of the positive electrode active material is not coated with a second coating layer, i.e., H2 is 0, and the secondary battery manufactured in Example 15 has B / A=1.5, so the cycle performance at 25°C of the secondary battery manufactured in Example 15 is 82% and the 4C multiplication performance is 85%. Comparing Example 1 and Example 30, in Example 30, the surface of the negative electrode active material is not coated with a first coating layer, i.e., H1 is 0, so the cycle performance at 25°C of the secondary battery manufactured in Example 30 is 80% and the 4C multiplication performance is 80%. Therefore, disposing a coating layer on the negative electrode active material can improve the cycle performance and multiplication performance of the secondary battery to a certain extent.
[0179] The above is a detailed description of the secondary battery and battery pack according to the embodiments of the present application, and the principles and embodiments of the present application are described using specific examples. The above description of the embodiments is for the purpose of helping to understand the technical solutions and their core ideas of the present application. Those skilled in the art should understand that some of the technical features described in the above embodiments may be modified or replaced with equivalents, and such modifications and replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of each embodiment of the present application.
Claims
1. a negative electrode sheet, the negative electrode sheet including a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, the negative electrode active material layer including a negative electrode active material, the negative electrode active material including a carbon material, The negative electrode active material has a grain size of XS nm; The non-Faraday capacity of the negative electrode sheet is Cdl nF, where 0.05≦Cdl≦10; ##EQU00011## That is, Secondary battery.
2. 0.01≦XS≦6; The secondary battery according to claim 1 .
3. The pore volume of the negative electrode active material is α cm 3 / g, and 0.5≦Cdl+10×α≦8. The secondary battery according to claim 1 .
4. The pore volume of the negative electrode active material is α cm 3 / g, and 0.001≦α≦0.5; The secondary battery according to claim 1 .
5. The negative electrode active material has a powder resistivity of R Ω·cm at 20 KN, and 0.01≦10R / Cdl≦5. The secondary battery according to claim 1 .
6. The negative electrode active material has a powder resistivity of R Ω·cm at 20 KN, and 0.002≦R≦2. The secondary battery according to claim 1 .
7. The secondary battery further includes a positive electrode sheet, the positive electrode sheet including a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, The particle size distribution of the negative electrode active material is A, and 0.5≦A≦2.
5. The secondary battery according to claim 1 .
8. The particle size distribution of the positive electrode active material is B, and 1.0≦B≦5.
0. The secondary battery according to claim 7.
9. 0.5≦B / A≦2.5; The secondary battery according to claim 8.
10. The thickness of the negative electrode active material layer is C μm, and 99 μm≦C≦160 μm. The secondary battery according to claim 7.
11. The thickness of the positive electrode active material layer is D μm, and 80 μm≦D≦130 μm. The secondary battery according to claim 10.
12. 0.1≦1−(D / C)≦0.5; The secondary battery according to claim 11.
13. The surface of the negative electrode active material is coated with a first coating layer, and the thickness of the first coating layer is H1 nm, where 5≦H1≦200 and 10≦Cdl×H1≦250. The secondary battery according to claim 1 .
14. The surface of the positive electrode active material is coated with a second coating layer, and the thickness of the second coating layer is H2 nm, and 5≦H2≦60; The secondary battery according to claim 7.
15. A secondary battery comprising the secondary battery according to any one of claims 1 to 14. Battery pack.
Citation Information
Patent Citations
Secondary battery and electrochemical device
CN115528206A
Smart system
JP2016061037A
Nonaqueous lithium power storage element
JP2018056410A
Power storage device
JP2019053996A